Digital Transformation Of Islamic Boarding Schools In Indonesia: Modernization, Innovation, and Value Preservation - Agus Alif Humaydiy; Iis Arifudin; Ria Yulia Gloria (IJGIE (International Journal of Graduate of Islamic Education), 2026)
The modernization of Islamic boarding schools (pesantren) is fundamentally an effort to transform educational institutions from traditional systems into more adaptive and innovative ones while maintaining the core values of Islamic teachings and the essential functions of pesantren. This study aims to examine the forms of modernization and innovation implemented by pesantren in the digital era and the challenges associated with these transformations. The study employed a library research approach by analyzing relevant academic literature on pesantren modernization, educational innovation, and digital transformation. Data were analyzed using thematic analysis. The findings reveal that pesantren modernization is manifested through curriculum innovation, the implementation of digital learning, the development of technology-based management systems, and the utilization of digital media for da’wah activities. Several pesantren have integrated digital technologies into educational practices through Learning Management Systems (LMS), digital libraries, hybrid learning models, and digital applications for the study of classical Islamic texts. These innovations contribute to broader access to knowledge, improved learning effectiveness, and more efficient institutional management. However, modernization also presents challenges related to digital literacy, infrastructure readiness, and the preservation of fundamental pesantren values, including adab (Islamic ethics), discipline, Islamic scholarly traditions, and the kiai–santri relationship. Therefore, pesantren modernization should be understood as a process of adaptation to technological advancement while remaining firmly rooted in the values and traditions of Islamic boarding school education.